Organizacija gradnje - Klanšek, Uroš (University of Maribor Press, 2023)
Construction Management. The topic of the textbook is divided into four main sections, which include introductory explanations, preliminary studies of construction conditions, planning of construction site arrangements and construction site organization project. The introductory chapter defines the concept of construction, the reasons for organizing the construction, the purpose and goal, and the approach to the implementation of this activity. The chapter on preliminary studies of construction conditions deals with contractual relationships, project documentation for construction, local conditions, construction calculations, technological process, operational plans, production factors and field conditions. The section on planning of construction site arrangements addresses the associated area, roads and paths, cranes, premises for workers, work equipment and objects, electrification, lighting, water supply and drainage, and handling of municipal waste water. The last section on the construction site organization project explains the accompanying plan, the estimate of preparatory and clean-up works, operational implementation plans, including safety and fire prevention measures.